The Development of Positive Attitudes towards Learning Mathematics in Primary School Students - Ludmila URSU (ACROSS)
This article approaches the problem of improving the development of attitudes towards learning mathematics in primary school students. It emphasizes the actuality and necessity of research based on educational policies documents, underlines the theoretical-methodological landmarks based on specialized literature analysis, and presents the methodology and the results of an experimental-ascertaining study of the development of attitudes towards learning mathematics in 4th graders. As a result, we underline the main students’ difficulties in the development of these attitudes which determine three main directions of their development. Finally, we present a model of didactic strategies of the specified attitudes development which admits different variants of class realization and propose a concrete example.